1984
DOI: 10.1029/jb089ib07p06049
|View full text |Cite
|
Sign up to set email alerts
|

East Pacific Rise from Siqueiros to Orozco Fracture Zones: Along‐strike continuity of axial neovolcanic zone and structure and evolution of overlapping spreading centers

Abstract: We have used the Sea Beam multibeam echo-sounding system to survey the East Pacific Rise (EPR) from 8ø20'N to 18ø30'N, obtaining complete coverage of the EPR axial neovolcanic zone and all intervening transform faults. Here we focus on the EPR neovolcanic zone and the definition of overlapping spreading centers (OCS's) between the Orozco and Siqueiros transform faults. The neovolcanic zone is narrow [0.5-2.0 kin) and continuous along strike and occurs within and near a strike-continuous axial summit graben. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
224
2

Year Published

1995
1995
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 345 publications
(234 citation statements)
references
References 74 publications
8
224
2
Order By: Relevance
“…The southern third of the northern segment, the western limb of the 11°45'N OSC, and the eastern limb of the 9"03'N OSC are also the only sections that have a triangular, uninflated cross-section and lack a summit caldera and a magma reflector (Macdonald and Fox, 1988) All of these features suggest that these sections are magma starved. By contrast, the other limbs of the OSC's, which are continuous with the next ridge segments to the north and south rather than with those in the survey area, appear to be magmatically robust (Macdonald et al, 1984).…”
Section: '40'mentioning
confidence: 91%
See 1 more Smart Citation
“…The southern third of the northern segment, the western limb of the 11°45'N OSC, and the eastern limb of the 9"03'N OSC are also the only sections that have a triangular, uninflated cross-section and lack a summit caldera and a magma reflector (Macdonald and Fox, 1988) All of these features suggest that these sections are magma starved. By contrast, the other limbs of the OSC's, which are continuous with the next ridge segments to the north and south rather than with those in the survey area, appear to be magmatically robust (Macdonald et al, 1984).…”
Section: '40'mentioning
confidence: 91%
“…While the eastern limb is broad and has a domed cross-section, an axial summit caldera, and a shallow magma reflector, it is deep ( >2750 m) . By contrast, the western limb is narrow and triangular and lacks a summit caldera and magma reflector, but it is relatively shallow (<2600 m) (Macdonald et al, 1984;Macdonald and Fox, 1988). A hydrocast (S-35) in the nodal basin, which lies between the two limbs of the OSC and exceeds 3160 m in depth, showed a hydrothermal plume maximum (4.4 nM Mn, 0.6 nM CH,) at the same water depth as those on the limbs, indicating that the plume almost certainly originated elsewhere and was carried over the basin by currents.…”
Section: Distribution Of Plumes Along the Northern Segmentmentioning
confidence: 99%
“…There is evidence both in support of, and against, a simple magma supply model as is illustrated in Figure 1 [Macdonald et al, 1984;Lonsdale, 1989b]. These variations in axial depth are associated with systematic changes in the shape of the axial high [Macdonald and Fox, 1988;Scheirer and Macdonald, 1993].…”
Section: Introductionmentioning
confidence: 88%
“…The stress field around the crack tip is then modified by the presence of the other cracks leading to kinked trajectories. In hierarchical fracturing processes [13], it is usually observed that cracks coalesce around a 90°angle, as for example in dessication [14][15][16] or in fault dynamics [17][18][19][20]. It has also been shown that two collinear approaching cracks (submitted to a uniaxial stress in mode I) can repel each other instead of merging tip to tip [21], resulting in a curved, "hookshaped" path.…”
mentioning
confidence: 99%